Tourist decision–making process in the selection of coastal tourism destination - Adeni, Nur Zakirah; A. Rahman, Muhammad Ali (IIUM Press, 2017)
Coastal tourism destination is a place where people can enjoy the scenery and experience loads of water based activities such as snorkeling, scuba diving and swimming. Tourists who seeks for these special kind of characters commonly will select the destination based on their preferences, needs and wants, due to the fact that different tourists have different types of behaviour. Apart from that, the tourists also differed in term of their culture and lifestyle. In order to choose the coastal tourism destination, the tourists are notably have high expectation, very demanding and very particular about the characteristic of the destination itself. Thus, the purpose of this book is to identify the major factor that influenced the tourist decision - making process in selecting or choosing the coastal tourism destination as the place for vacation. Factors determination are vital because it may assist the tourism marketer or tourism service provider in enhancing the quality of services and improving their management of the coastal tourism destination in order to attract more tourists come. In order to identify and analyze the main factor that influence tourists’ decision – making process, questionnaire survey was distributed to 50 respondents specifically for Malaysian tourist or local domestic tourist. The random sampling was used by researcher in order to collect the relevant data. Furthermore, secondary data which is the feedback from the experienced tourist was also used in order to avoid bias information from the respondents. As the data has been gathered and analyzed, it can be found that the main factor that influence the tourists in their decision – making process is the relaxation purposes. Perhentian Island is one of the coastal tourism destination that rich with the white sandy beaches and enjoyable activities. There is no doubt that majority of the tourists choose the Perhentian Island as their place of vacation. This is due to the atmosphere of calmness and excitement activity at the Perhentian Island itself.